2013
DOI: 10.1145/2542182.2542189
|View full text |Cite
|
Sign up to set email alerts
|

Personalized emerging topic detection based on a term aging model

Abstract: Twitter is a popular microblogging service that acts as a ground-level information news flashes portal where people with different background, age, and social condition provide information about what is happening in front of their eyes. This characteristic makes Twitter probably the fastest information service in the world. In this article, we recognize this role of Twitter and propose a novel, user-aware topic detection technique that permits to retrieve, in real time, the most emerging topics of discussion e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…Related to the relation between the user's interests and the trending topics, Cataldi et al proposed a reranking approach that makes use of the users' activity and the posts' contents to personalize the emerging topics [27]. This is done by monitoring the usage of the keywords appearing in the tweets over time, and comparing its importance with the user's context, in order to highlight the most emerging topics within the user's interests.…”
Section: Trending Topics In Social Networkmentioning
confidence: 99%
“…Related to the relation between the user's interests and the trending topics, Cataldi et al proposed a reranking approach that makes use of the users' activity and the posts' contents to personalize the emerging topics [27]. This is done by monitoring the usage of the keywords appearing in the tweets over time, and comparing its importance with the user's context, in order to highlight the most emerging topics within the user's interests.…”
Section: Trending Topics In Social Networkmentioning
confidence: 99%
“…Glänzel and Thijs (2012) presented the use of core documents to discover emerging topics by analyzing the cross-citations between core documents and clusters of disciplines in different periods. Cataldi et al (2013) utilized a novel term aging model to compute the burstiness of each term on Twitter to enable users to search for the emerging topics they are interested in. Chen (2013) found that latent domain knowledge was usually highly relevant but received lower citation than mainstream domain knowledge.…”
Section: Related Researchmentioning
confidence: 99%
“…Problems related to clustering in social media platforms include the identification of topics or memes [33,47,53], and event detection in social streams [8,11,32,34,49]. Meme and topic identification techniques usually emphasize the terms and keywords as signatures of the content.…”
Section: Related Workmentioning
confidence: 99%